Pengaruh Brand Image dan Brand Awareness Merek Motor Yamaha terhadap Minat Pembelian - Farel Reyhan Albion; Mirzam Arqy Ahmadi (Universitas Serambi Mekkah, 2025)
The rapid development of the industry has led to increasingly fierce business competition. Consumers are often faced with a wide selection of brands offering products with similar features and prices. Likewise, competition in the automotive industry is fierce, so every motorcycle brand company strives to build a strong image and be recognized by consumers, such as brand image and brand awareness. Understanding the effect of brand image and brand awareness on purchase intention is important, both for companies to formulate marketing strategies and for consumers to make purchasing decisions. The purpose of this study was to determine the effect of brand image and brand awareness on purchase intention of the Yamaha motorcycle brand. The research method used is qualitative with a literature study approach from existing relevant sources, such as literature, books, journals, and others. The results showed that there was a positive and significant influence of brand image and brand awareness variables on the purchase intention of the Yamaha motorcycle brand.